California sketches - Chard, Thomas S. (Chicago, 1888)
Thomas S. Chard made a rail journey from Chicago to California in 1888. California sketches (1888) describes the sights seen during his busy five-week stay: San Francisco, Monterey, San José, Yosemite, Los Angeles, San Diego, and the Geysers.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Description and travel